Knee extension strength and hamstrings-to-quadriceps imbalances in elite soccer players - Bogdanis, G. C.; Kalapotharakos, V. I. (International Journal of Sports Medicine, 2016)
This study examined the relationship between hamstrings-to-quadriceps strength ratio (H:Q) and relative strength of the knee extensors in elite soccer players. Peak torque was measured during isokinetic knee extension/flexion at angular velocities of 60°·s-1, 180°·s-1 and 300°·s-1. 18 professional players were divided into 2 groups, depending on their H:Q at 60°·s-1. Players in the lower H:Q group (n=7) had significantly smaller H:Q ratios compared with the higher H:Q group (n=11) at all angular velocities (60°·s-1: 49.2%; 95% CI: 61.3-57.8% vs. 59.5%; 95% CI: 52.2-46.2%, p=0.001). Players in the lower H:Q group had greater knee-extension peak torque compared with the higher H:Q group (60°·s-1: 313; 95% CI: 335-291 vs. 269; 95% CI: 289-250?N·m, p=0.01). No differences were found in hamstrings` strength between the 2 groups (60°·s-1: 156; 95% CI: 170-143 vs. 160; 95% CI: 173-148 N·m, p=0.96). Negative correlations between knee extension peak torque and H:Q ratio were observed at all angular velocities (r=-0.65 to -0.67, p<0.01). In conclusion, a low H:Q strength ratio measured during isokinetic strength testing in professional soccer players, is observed mainly in those with strong quadriceps muscles, while players with lower quadriceps strength have H:Q ratios around the recommended values.